PERBANDINGAN KADAR SATURASI OKSIGEN HARI PERTAMA DAN HARI KETIGA PADA BAYI BARU LAHIR - Kaunang, Adriaan W.; Wilar, Rocky; Rompis, Johnny (e-CliniC, 2015)
Abstract: Every cells in human body needs oxygen to implement metabolism function, therefore the process maintenance oxygenation is an effort to determine the needs of supply oxygen to every cells in human body. Oxygen saturation is one of a value that we must consider on determine the needs of supply oxygen in our body especially in newborn because when the oxygen saturation is low will reduce the supply oxygen to cells. The result of paired T-test says that there are significant changes between first day and third day of oxygen saturation in newborn (p <0,001).Keywords. oxygen saturation, newbornAbstrak: Setiap sel tubuh manusia membutuhkan oksigen untuk melaksanakan fungsi metabolisme, sehingga mempertahankan oksigenasi adalah upaya untuk memastikan kecukupan pasokan oksigen ke jaringan atau sel. Saturasi oksigen merupakan salah satu hal yang patut kita perhatikan dalam penilaian kecukupan pasokan oksigen pada tubuh kita terutama pada bayi baru lahir karena ketika saturasi oksigen rendah maka mengakibatkan pasokan oksigen ke jaringan berkurang. Hasil uji t berpasangan menyatakan ada perbedaan yang sangat bermakna (p < 0,001).Kata kunci: saturasi oksigen, bayi baru lahir